FROM POLITICAL ACTOR TO THE BLACK EDUCATOR MOVEMENT: COLLECTIVES AS PLACES OF BLACKNESS AT UFRJ (Práxis Educativa, 2022)
In this article, we identify in the intervention of black collectives the dynamics of constitution of places of blackness and conformation a black territoriality as a formative matrix at UFRJ. We contemplate, through these places of blackness, three movements that make black subjects: they start from being adrift, land through the quilombo and, finally, accommodate existences and produce knowledge. This matrix gives foundation and specificity to the corporeal identity, political and aesthetic knowledge that this movement forges. It allows the production of new knowledge in health, as we have seen, in the experience of student groups in the area. Investigating the conformation of black territorialities can favor the examination of political-pedagogical singularities, educational practices and the types and scope of knowledge produced by the black movement in our universities.Keywords: Black Collectives; Places of Blackness; Black Educator Movement